PARTISIPASI AYAH TERHADAP POSYANDU AYAH PEDULI BALITA DALAM UPAYA PELAYANAN KESEHATAN BALITA THE PARTICIPATION OF FATHER ON FATHER’S POSYANDU IN CARING THE CHILDREN UNDER FIVE TO THE EFFORT OF HEALTH CARE SERVICES - Maryati, Heni; Prihatini, Monika Sawitri (WARTA BHAKTI HUSADA MULIA : Jurnal Kesehatan, 2018)
ABSTRACT One of the way in health development that will be pursued until 2025 is all of the residents / environment has had at least one active posyandu that carry out the activities at least once in a month. It most generally that it is dominated by women. But different things happened in father’s Posyandu in caring the children under five become the first childhood posyandu in Jombang that accommodate the participation of father. This study aims to see how the participation of fathers and men to father’s posyandu in caring the children under five in the efforts of health services of children under five in father’s posyandu in caring the children under five and factors that affect the participation of the fatherin Rejoagung Village Ploso District Jombang.This study used descriptive with qualitative approach. The analysis unit of in this study was the father and men’s cadre who participated in father’s posyandu in caring the children under five. The data collection technique used literature study, observation and direct interview.The result of study showed that there were some forms of participation done by the father and men’s cadre to father’s the posyandu in caring children under five, such as the participation of health workers, money, and participate in the implementation of the program. This was influenced by some internal and external factors, such as knowledge, length of stay, age, occupation, habits, needs, family, location of posyandu, and the benefits of participating in posyandu activities. In order to reach the golden age,it hoped the cadre of posyandu give innovation,find new ways to face the problem Keywords: Father’s participation, Posyandu, Health services for children under five